2022
DOI: 10.1098/rspb.2022.0844
|View full text |Cite
|
Sign up to set email alerts
|

Brain morphology correlates of learning and cognitive flexibility in a fish species ( Poecilia reticulata )

Abstract: Determining how variation in brain morphology affects cognitive abilities is important to understand inter-individual variation in cognition and, ultimately, cognitive evolution. Yet, despite many decades of research in this area, there is surprisingly little experimental data available from assays that quantify cognitive abilities and brain morphology in the same individuals. Here, we tested female guppies ( Poecilia reticulata ) in two tasks, colour discrimination and reversal learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 71 publications
(111 reference statements)
0
19
0
Order By: Relevance
“…Based on artificial selection, the results show how telencephalon expansion through mosaic brain evolution can improve executive functions. In both the reversal learning and detour tasks, a relatively larger telencephalon appeared to correlate positively with performance in these two tasks (see also Triki et al ( 34 , 44 )). This suggests that relative telencephalon size facilitated flexible learning.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Based on artificial selection, the results show how telencephalon expansion through mosaic brain evolution can improve executive functions. In both the reversal learning and detour tasks, a relatively larger telencephalon appeared to correlate positively with performance in these two tasks (see also Triki et al ( 34 , 44 )). This suggests that relative telencephalon size facilitated flexible learning.…”
Section: Discussionmentioning
confidence: 83%
“…Interestingly, we detect no differences in our nonexecutive function assay, the color discrimination learning. This might be because this task does not require complex processing but rather basic association formation through operant conditioning ( 44 ). This is consistent with the findings from fish whose entire telencephalon being ablated can still perform successfully in simple associative learning tasks ( 57 ), while they failed in more complex tasks like reversal learning ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lack of any effects of telencephalon size could be because we have not yet been able to generate enough divergence between the large and small telencephalon size selected lines. However, we have previously found that the existing divergence in telencephalon size affects several aspects of cognition ( Triki et al 2022 , 2023 ). This includes several advanced cognitive abilities such as detour learning, reversal learning and working memory that were enhanced in the large compared to the small telencephalon size selection lines ( Triki et al 2022 , 2023 ).…”
Section: Discussionmentioning
confidence: 98%
“…The study of neurotoxic effects due to exposure of animals to anthropogenic contaminants primarily involves analyzing alterations in their behavioral phenotypes. Behaviors are increasingly recognized as sensitive and early indicators of sublethal chemical risks in exposed animals, representing highly integrative endpoints that encompass a wide range of complex developmental and physiological processes. , Despite the increasing use of behavioral assays in aquatic eco-neurotoxicology, one of the least studied aspects is the impact of pollutants on cognitive behaviors. Memory and learning represent the highest-level neurological functions that have been reported in a wide range of taxa, including larval stages of fish and amphibians. , Moreover, recent studies have demonstrated that aquatic invertebrates, such as planarians, mollusks, and arthropods, also exhibit various levels of memory and learning despite some controversies related to historical methodological errors. As such, there has been a notable resurgence of interest in cognitive research using several promising aquatic models, such as planarians, zebrafish ( Danio rerio ), guppy fish ( Poecilia reticulata ), and tadpoles of the African clawed frog ( Xenopus laevis ). ,, …”
Section: Introductionmentioning
confidence: 99%